Abnormal B-Cell and Tfh-Cell Profiles in Patients With Parkinson Disease: A Cross-sectional Study. Issue 2 (24th March 2022) - Li, Rui; Tropea, Thomas Francis; Baratta, Laura Rosa; Zuroff, Leah; Diaz-Ortiz, Maria E.; Zhang, Bo; Shinoda, Koji; Rezk, Ayman; Alcalay, Roy N.; Chen-Plotkin, Alice; Bar-Or, Amit
Abstract : Background and Objectives: There has been growing interest in potential roles of the immune system in the pathogenesis of Parkinson disease (PD). The aim of the current study was to comprehensively characterize phenotypic and functional profiles of circulating immune cells in patients with PD vs controls. Methods: Peripheral blood was collected from patients with PD and age- and sex-matched neurologically normal controls (NCs) in 2 independent cohorts (discovery and validation). Comprehensive multicolor flow cytometry was performed on whole blood leukocytes and peripheral blood mononuclear cells to characterize different immune subsets and their ex vivo responses. Results: The discovery cohort included 17 NCs and 12 participants with PD, and the validation cohort included 18 NCs and 18 participants with PD. Among major immune cell types, B cells appeared to be preferentially affected in PD. Proliferating B cell counts were decreased in patients with PD compared with controls. Proportions of B-cell subsets with regulatory capacity such as transitional B cells were preferentially reduced in the patients with PD, whereas proportions of proinflammatory cytokine-producing B cells increased, resulting in a proinflammatory shift of their B-cell functional cytokine responses. Unsupervised principal component analysis revealed increased expression of TNFα and GM-CSF by both B cells and T cells of patients with PD. In addition, levels of follicular T cells, an important B-cell helper T-cell population, decreased in the patients with PD, correlating with their B-cell abnormality. Discussion: Our findings define a novel signature of peripheral immune cells and implicate aberrant Tfh:B-cell interactions in patients with PD.